2021
DOI: 10.1016/j.lanwpc.2021.100205
|View full text |Cite
|
Sign up to set email alerts
|

The double burden of malnutrition and dietary patterns in rural Central Java, Indonesia

Abstract: Background: Indonesia is undergoing a nutrition transition (NT) comprised of rising rates of overweight/obesity and consumption of high fat food/snacks but is still struck by undernutrition, causing a double burden of malnutrition. Little research pertains to the double burden of malnutrition and its associations with diet in rural Indonesia using primary village level data.Methods: We conducted a 24-hour food recall and food frequency questionnaire and assessed anthropometric status of rural villagers from fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 33 publications
3
19
0
5
Order By: Relevance
“…This is because whilst issues of non-compliance and inconsistent use of Fe supplementation in Indonesia have been reported (11) , the consumption of soybean in our study was almost 80 %, which was expected given it is a local staple (Table 1). Whilst Fe fortification of wheat flour has been mandatory in Indonesia since 2001 (44) , consumption of wheat flour products among adults in our study was very low; the dominant carbohydrate source was white rice (45) . Only recently has Fe fortification of rice programmes began in Indonesia, but with limited success in increasing serum Hb and ferritin levels (44) .…”
Section: Discussionmentioning
confidence: 66%
“…This is because whilst issues of non-compliance and inconsistent use of Fe supplementation in Indonesia have been reported (11) , the consumption of soybean in our study was almost 80 %, which was expected given it is a local staple (Table 1). Whilst Fe fortification of wheat flour has been mandatory in Indonesia since 2001 (44) , consumption of wheat flour products among adults in our study was very low; the dominant carbohydrate source was white rice (45) . Only recently has Fe fortification of rice programmes began in Indonesia, but with limited success in increasing serum Hb and ferritin levels (44) .…”
Section: Discussionmentioning
confidence: 66%
“…Several other studies have also revealed that Indonesian adults insufficiently consumed protein, fruits, and vegetables, but consumed fast food and sodium excessively [41]. Another study that has been conducted in Central Java, Indonesia, also showed that dietary patterns were associated with increased consumption of soft drinks, snacks, and various animal products [43]. Another study was further conducted in Jakarta showing that the daily food consumption of the observed population reached 1868-2334 g/capita/day.…”
Section: Food Consumption In Indonesiamentioning
confidence: 93%
“…Masalah stunting dan gizi kurang masih menjadi fokus oleh pemerintah untuk terus diturunkan kasusnya, namun di saat yang bersamaan prevalensi gizi lebih meningkat pada kelompok usia anak di Indonesia (Rachmi et al, 2016). Masalah gizi kurang banyak terjadi pada anakanak sedangkan masalah gizi lebih banyak ditemukan pada usia dewasa (Lowe et al, 2021).…”
Section: Pendahuluanunclassified